Structural Variation and Preference in Lanthanide-pyridine-2,6-dicarboxylate Coordination Polymers - Chuasaard T. (2017)
© 2017 American Chemical Society. Ten lanthanide coordination polymers were designed and synthesized using pyridine-2,6-dicarboxylic acid (H 2 pdc) and two different heating techniques (conventional and microwave): [Ln(pdc)(H 2 O) 4 ] 3 ·3Cl {Pa3; Ln = Pr (I), Nd (II), Sm (III), Eu (IV), and Gd (V)}, [Ln(pdc)(Hpdc)(H 2 O) 2 ]·3H 2 O {P2 1 /c; Ln = Pr (VI), Nd (VII), and Sm (VIII)} and [Ln(pdc)(H 2 O) 4 ] 3 ·3Cl {Ia3; Ln = Sm (IX), and Eu (X)}. These complexes show variation in structures depending on the heating technique and the lanthanide ions. They can be classified into the cubic Pa3 (I-V) and Ia3 (IX, X), and the monoclinic P2 1 /c (VI-VIII) complexes. The cubic complexes exhibit supramolecular isomerism and a tubular three-dimensional structure of interpenetrated lcs and pcu net topologies, while the monoclinic complexes are the supramolecular assemblies of the one-dimensional chains. As the cubic Pa3 structures are favored by the use of the microwave, there is variation in structures as conventional heating was employed, although the cubic Pa3 structures are still the most favored except for the VI case. The title complexes showed moderate thermal stabilities. The organic ligand is revealed to be a modest sensitizer to initiate the photoluminescence in the title complexes.